Sustentabilidade ambiental na universidade federal do pampa: uma aplicação do UI Greenmetric - Charão, Rejane Miqueli Galarça (2025)
Sustainability has been gaining prominence in universities, assuming a central role in citizen education and institutional management. However, the practical implementation of sustainable initiatives still presents gaps at many Brazilian universities. The Federal University of Pampa (UNIPAMPA), the focus of this study, has developed initiatives in this regard, but lacks a systematic evaluation of its practices to identify progress, weaknesses, and opportunities for improvement. This research gap motivated this investigation, seeking to understand the extent to which the university adopts and consolidates sustainability-oriented actions, especially when analyzed using internationally recognized metrics. The overall objective of this study was to identify whether UNIPAMPA, based on UI GreenMetric, cultivates sustainability-oriented initiatives, demonstrating a commitment to the environment. To achieve this objective, the document analysis method was employed, gathering institutional data related to sustainability across all ten of the university's campuses. The data collection instrument was based on the official UI GreenMetric World University Ranking 2024 questionnaire, adapted to reflect UNIPAMPA's multi-campus reality, allowing for a more accurate assessment of the institution's specificities and challenges. The results demonstrate that UNIPAMPA is aware of the importance of sustainable actions and projects, evidenced by the existence of practices aligned with the ranking criteria, covering infrastructure, energy, waste, water, transportation, and education and research. Despite this, opportunities for improvement were identified, particularly in increasing the number and diversity of sustainable actions, as well as in enhancing existing initiatives. As a contribution, this study provides UNIPAMPA with a comprehensive diagnosis that can support strategic decisions and strengthen the institution's socio-environmental management. The survey allows the university to identify which practices are consolidated, which require expansion, and which still need to be implemented, promoting a more integrated approach across its campuses. Furthermore, it promotes internal reflection, academic debate, and community engagement around sustainability, encouraging the institution's effective participation in UI GreenMetric, with a view to consolidating its position as a leading university in the field.